2017
DOI: 10.1016/j.amsu.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Porocarcinoma; presentation and management, a meta-analysis of 453 cases

Abstract: Backgroundporocarcinoma is a rare sort of skin cancer developing from sweat glands. Its clinical course and management are not well understood.Objectivesthe current meta-analysis is to address the presentation and management of porocarcinoma.Data sourcesWeb of Science, PubMed, MEDLINE on OVID and Google scholar were searched for English-language studies published before December 1, 2016.ResultsThe review of literature revealed 453 cases. From which 222 (49%) cases were male and female were 231 (51%). The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
191
2
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(238 citation statements)
references
References 102 publications
13
191
2
12
Order By: Relevance
“…Since the first description of PC by Pinkus and Mehregan, approximately 500 cases have been documented in the literature 3. A recent UK study demonstrated a rapid rise in PC incidence in the East of England,4 and using age-standardised incidence rates, estimated a rapidly increasing number of cases likely to be diagnosed over the next decade. It is possible that this trend reflects greater diagnostic awareness of the tumour morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first description of PC by Pinkus and Mehregan, approximately 500 cases have been documented in the literature 3. A recent UK study demonstrated a rapid rise in PC incidence in the East of England,4 and using age-standardised incidence rates, estimated a rapidly increasing number of cases likely to be diagnosed over the next decade. It is possible that this trend reflects greater diagnostic awareness of the tumour morphology.…”
Section: Discussionmentioning
confidence: 99%
“…As PC is so rare, epidemiological data vary widely across small case series. A recently published meta-analysis of 453 patients reported 49% of cases were male, and 51% were female 4. The mean age was 67.5 years old, with most patients diagnosed in their seventh and eighth decades.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of the EPC is variable. Patients usually present with a nodule (71%), ulcerated lesion (18%), or plaque (10%) 6 . The asymptomatic or painful lesion may have a wide spectrum of colors, ranging from reddish to black 10‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…According to gender, this type of carcinoma is distributed evenly (49% in men and 51% in women). Its average age of onset is the seventh and eighth decade of life (average age of 67 years) [2]. The most frequent clinical presentation is a nodule (71% of cases), associated with warty epidermal changes and/or ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, tumors are characterized by rapid growth, ulceration, bleeding, or pain [4]. The average duration of the presentation is five years, and its most frequent location is head and neck (39%), and lower limbs (33%) [2]. Few reports in the literature describe cases of porocarcinoma in unusual places, such as vulva, soft tissue, and eyelid.…”
Section: Discussionmentioning
confidence: 99%